Maternal Diabetes and Postnatal High-Fat Diet on Pregnant Offspring - Sinzato, Yuri Karen; Paula, Verônyca Gonçalves; Gallego, Franciane Quintanilha; Moraes-Souza, Rafaianne Q.; Corrente, José Eduardo; Volpato, Gustavo Tadeu; Damasceno, Débora Cristina (Frontiers in Cell and Developmental Biology, 2022)
Maternal diabetes-induced fetal programming predisposes offspring to type 2 diabetes, cardiovascular disease, and obesity in adulthood. However, lifelong health and disease trajectories depend on several factors, and nutrition is one of the main ones. We intend to understand the role of maternal diabetes-induced fetal programming and its association with a high-fat diet during lifelong in female F1 generation focusing on reproductive outcomes and the possible changes in physiological systems during pregnancy as well the repercussions on F2 generation at birth. For this, we composed four groups: F1 female-pups from control (OC) or from diabetic dams (OD) fed with standard (SD) or high-fat diet (HFD) from weaning to full-term pregnancy. During pregnancy, glucose intolerance and insulin sensitivity were evaluated. In a full-term pregnancy, maternal blood and liver were collected to evaluate redox status markers. Maternal blood, placental tissue, and fetal blood (pool) were collected to evaluate adiponectin and leptin levels. Maternal reproductive parameters were evaluated as well. Maternal diabetes and high-fat diet consumption, in isolation, were both responsible for increased infertility rates and fasting glucose levels in the F1 generation, and fetal growth restriction in the F2 generation. The association of both conditions showed, additionally to those, increased lipoperoxidation in maternal erythrocytes, regardless of the increased endogenous antioxidant enzymes activities, glucose intolerance, decreased number of implantation sites and live fetuses, decreased litter, fetal and placental weight, increased pre-implantation losses, and increased fetal leptin serum levels. Thus, our findings show that fetal programming caused by maternal diabetes or lifelong high-fat diet consumption leads to similar repercussions on pregnant rats. In addition, the association of both conditions was responsible for glucose intolerance and oxidative stress in the first generation and increased fetal leptin levels in the second generation. Thus, our findings show both, F1 and F2 generations harmed health after maternal hyperglycemic intrauterine environment and exposure to high-fat diet from weaning until the end of pregnancy.